Developing democracy or promoting disruption?: educators' perceptions of the Department of Education's current policy on classroom discipline - Davidowitz, Orit (My University, 2009)
ABSTRACT Before 1994 corporal punishment was the main discipline strategy implemented in schools. Since then legislation has been passed, which resulted in corporal punishment being made illegal. The majority of educators strongly opposed this change in the national discipline policy as they felt it left them powerless in terms of disciplining their learners. In 2000 a national programme on discipline strategies was embarked on and many of the results were incorporated in the booklet titled “Alternatives to Corporal Punishment: The Learning Experience.” This booklet formed part of the National Department of Education’s discipline policy. It contains guidelines for implementing alternative strategies to corporal punishment in an effort to remediate problems with discipline. It also gives examples of disciplinary action for dealing with misconduct. The objective of this research was to establish what educators’ perceptions of the Department of Education’s alternative methods to corporal punishment are after they had exposure to it by means of a workshop. The research also aimed to explore underlying reasons for the educators’ perceptions. The sample of sixty-four educators used for this purpose came from various school contexts from traditional ex-model C schools to historically disadvantaged schools. The data in this study was obtained by means of a structured questionnaire, which was administered to the educators that attended the workshop on the Department of Education’s Discipline policy. In view of the fact that there are no existing instruments in use to explore the objectives of this research, it was necessary to develop a questionnaire. The questionnaire consisted of both open-ended questions, which required a more qualitative approach as well as close-ended questions, which were more quantitative in nature. The results obtained from this study showed that the majority of the respondents who attended the workshop agreed with the discipline policy proposed by the Department of Education. However, there was a significant discrepancy between the educators’ perceptions of the policy and whether they felt it could be successfully implemented in their schools. The main reasons for this was that the respondents felt that the Department of Education and educator training institutions do not provide educators with adequate discipline training and support. Furthermore, the findings of this study demonstrated that the respondents are experiencing a state of learned helplessness where they feel the discipline problems they are faced with are beyond their control.
Keywords: discipline; discipline policy; social-behavioural theory; educator; Department of Education, South Africa; democratic discipline; code of conduct; learner